NEWBORN PHYSIOLOGICAL PARAMETERS AND EARLY INITIATION OF BREASTFEEDING - Salmadina, Hanin Tsabitah; Naimah, Naimah; yuliani, ita (Jurnal Pendidikan Kesehatan, 2026)
Early initiation of breastfeeding (IMD) is an important first step in providing exclusive breastfeeding and has various benefits for infant health. However, IMD coverage in East Java Province in 2019 was still below the national target of 67.7% (Ministry of Health, 2020). This study aims to determine the relationship between IMD and physiological parameters of newborns. This study used an observational analytical design with a cross-sectional approach. The population was newborns at the Independent Midwife Practice (TPMB) in Malang in April–May 2024. A sample of 42 respondents was drawn using a purposive sampling technique. Secondary data were collected using documentation sheets, then analyzed univariately and bivariately using the Spearman Rank test. The results showed that the majority of infants who underwent IMD had stable physiological parameters: 85% had normal body temperature, and 100% had normal heart rate and respiratory rate. Statistical tests showed a significant relationship between early breastfeeding initiation (IMD) and infant body temperature (p=0.019), heart rate (p=0.000), and respiratory rate (p=0.048). These results indicate that IMD has a positive effect on the stability of newborn physiological parameters. Therefore, it is important for health workers, especially midwives, to optimize the implementation of early breastfeeding initiation (IMD) for newborns without emergency indications. Keywords: Early initiation of beastfeeding, physiological parameters, newborns